Prospective Teachers' Problem Solving Skills and Self-Confidence Levels - (:unkn) unknown (EDAM, 2008)
The basic objective of the research is to determine whether the education that prospective teachers at different fields receive is related to their levels of problem solving skills and self-confidence. Within the mentioned framework, the prospective teachers' problem solving and self confidence levels have been examined under several variables. The research sampling has been formed by 162 students who are currently studying for their bachelor's degree in Marmara University, Ataturk Faculty of Education (n = 92 Music, n = 70 PCG). 70.7% of Music Teaching Department students are females, 29.3% are males and 69.6% is between 18-22 ages. 52.9% of Psychological Counseling and Guidance students are females, 47.1% is males and 97.1% of them consist of the students within this age group. The Problem Solving Inventory developed by Heppner and Peterson (1982) and the Piers-Harris Self-Concept Scale adapted to Turkish by Catakli and Oner and Individual Information Form has been utilized in the research. The data of the research have been analyzed by, t-test, Kruskal Wallis-H, and Mann Whitney U tests. The findings have introduced that there are statistical differences in the aspect of some sub-dimensional values for both scales (Avoidance: t = -2.330; p < .05, Individual Control: t = -1,975; p < .05, Behavior: t = 2.009; p < .05, Intelligence and school status: t = -2.496; p < .05, Coming into Favor: t = 2.487; p < .05) and it has been revealed that the relations between students' self confidence and problem solving skills are negative. As a result, although correlation between two variables showed opposite relation, one variable is not decisive in the other.
Keywords: Education; Problem Solving Skills; Self-Confidence